2022
DOI: 10.3390/s22031187
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Perceptual Load and Cognitive Load by Fixation-Related Information of Eye Movements

Abstract: Assessing mental workload is imperative for avoiding unintended negative consequences in critical situations such as driving and piloting. To evaluate mental workload, measures of eye movements have been adopted, but unequivocal results remain elusive, especially those related to fixation-related parameters. We aimed to resolve the discrepancy of previous results by differentiating two kinds of mental workload (perceptual load and cognitive load) and manipulated them independently using a modified video game. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 30 publications
4
20
0
Order By: Relevance
“…Probably, participants lengthened their initial fixations to process words more carefully, and as a result, needed less subsequent fixations on a word, which reduced GD. This pattern of eye movements under noise is in line with previous observations of eye-movement behavior under increasing cognitive load in [37,38].…”
Section: Interim Discussionsupporting
confidence: 92%
“…Probably, participants lengthened their initial fixations to process words more carefully, and as a result, needed less subsequent fixations on a word, which reduced GD. This pattern of eye movements under noise is in line with previous observations of eye-movement behavior under increasing cognitive load in [37,38].…”
Section: Interim Discussionsupporting
confidence: 92%
“…The longer fixation duration in the as-built scenario means that pedestrians spent a long time on searching the environment and potential hazards. As reported by previous studies, longer fixation duration and lower fixation rate is related to higher cognitive load 34 . An earlier pedestrian eye tracking study also found that 'safe' pedestrians have a lower mean fixation duration than 'rogue' pedestrians after they get used to the environment 35 .…”
Section: Discussionsupporting
confidence: 50%
“…In turn, in the PTs test, the occurrence of statistically significant differences between the variants was found in the Digit test (for parameters related to blinking: BDA, BDX, BDM) and the Fraction test (for BDA, FDA and SF parameters). As proved in the publication [31] perceptual load and cognitive load had an opposite effect on fixation duration. Higher perceptual load led to decreased fixation durations but higher cognitive load led to increased fixation durations.…”
Section: Discussionmentioning
confidence: 77%
“…pupil diameter and eye blink rate or blink frequency as a cognitive function indicators [20, 21, 22]. Studies investigating the potential of using eye movements for assessing the mental workload also indicate that pupil diameter and fixation time show an increase if the mental workload increases while saccade distance and saccade speed do not show any differences [23, 24]. Other scientific literature shows that saccade distance and saccade speed can be used as an indicator of mental workload [25].…”
Section: Introductionmentioning
confidence: 99%